Books on Asia from the Near East to the Far East - Birnbaum, Eleazar (Book collections on Project MUSE., 2014)
This is a selected, annotated list of some 2,000 books on Asia in English and French currently in print, chosen with the aim of providing a long-term historical perspective for the general reader.